Isolation of acidophilic bacteria from acid drainage from nearby mining units Julcani and Salvage , Huancavelica - Arias, Vladimir (2012)
Effluent from rock and mine are characterized by their acidity and dissolved metals, are usually natural habitat of bacteria of the genus and able to get energy from oxidative catalysis bacteria widely studied for their importance in the biooxidation of minerals and sulfur compounds , iron , and metal sulfides . The study samples come from the region of Huancavelica nearby mining units Julcani and Salvage ; achieving isolation in 9k modified and FeO solid agar and identified by light microscopy for the presence of oxidizing acidophilic bacteria consortium of liquid media. The comparison of these results was performed by the chain reaction of the polymerase at 98 % probability.